Climate Warming Will Exacerbate Unequal Exposure to Compound Flood‐Heatwave Extremes - Qikang Zhao; Liang Gao; Qingyan Meng; Mingming Zhu (Earth's Future)
Abstract Compound flood‐heatwave extremes (CFHWs) have threatened the sustainable development of human society and ecosystems. However, the disproportionate risks in regions with different economic development under a warming climate have not been quantified. This study carries out a global investigation on the future CFHWs under three scenarios based on 11 models from the Coupled Model Intercomparison Project Phase 6 (CMIP6). Results reveal a 7.5‐fold increase in global annual CFHW days by 2100 under the intermediate greenhouse‐gas‐emission scenario SSP2‐4.5 compared to that in 1980. Under SSP2‐4.5, population exposure in low‐income countries in the late future (2071–2090) will be about 9‐fold higher than in high‐income countries compared to baseline period (1995–2014). Moreover, exposure of the poor groups living on less than $6.85/day will increase by nearly 28.1‐fold. Eastern Africa and South Asia are identified as particularly high‐risk regions, where large populations living in poverty face rapidly increasing CFHWs. These findings indicate that climate inequality will become more pronounced if climate warming continues without immediate effective measures. Our study also underscores the urgent need for mitigation and adaptation strategies against the future increasing CFHWs, especially for the vast low‐income and high‐risk regions.